ANALISIS SEMIOTIKA ROLAND BARTHES DALAM IKLAN ARAB عصائر (JUS) PADA BRAND KDD - Sheila Rizka Awalia; Fatimatuzzahra Nasution, Sri Rizki Maulida Tanjung, Rafiza Azhar, Siti Mandala Putri Sagala (CV. ADIBA AISHA AMIRA, 2025)
This research aims to analyze Arabic juice advertisement on KDD brand using Roland Barthes semiotic approach. This advertisement was chosen because it is able to create a strong message and touch consumers through the symbols contained in the visuals and text. Using Barthes' semiotic theory, which relies on the concepts of sign, denotation, and connotation, this research focuses on how the ad constructs meaning through the use of images, colors, and words. The analysis process involved identifying key signs in the ad, which were then associated with layers of emerging meanings, both direct (denotative) and deeper (connotative). The results show that KDD advertisements utilize cultural symbols and traditional values associated with freshness and product quality, which in turn strengthen the brand image in the eyes of consumers. The analysis also reveals how the ads manipulate hidden messages to form a more emotional understanding and bond consumers with the product. Overall, this research provides a deeper understanding of the use of semiotics in marketing strategies in the world of advertising.